PCASTt/SPCG-17—a randomised trial of active surveillance in prostate cancer: rationale and design. Issue 8 (22nd August 2019) - Ahlberg, Mats Steinholtz; Adami, Hans-Olov; Beckmann, Kerri; Bertilsson, Helena; Bratt, Ola; Cahill, Declan; Egevad, Lars; Garmo, Hans; Holmberg, Lars; Johansson, Eva; Rannikko, Antti; Van Hemelrijck, Mieke; et al.
Abstract : Introduction: Overtreatment of localised prostate cancer is substantial despite increased use of active surveillance. No randomised trials help define how to monitor patients or when to initiate treatment with curative intent. Methods and analysis: A randomised, multicentre, intervention trial designed to evaluate the safety of an MRI-based active surveillance protocol, with standardised triggers for repeated biopsies and radical treatment. The aim is to reduce overtreatment of prostate cancer. 2000 men will be randomly allocated to either surveillance according to current practice or to standardised triggers at centres in Sweden, Norway, Finland and the UK. Men diagnosed in the past 12 months with prostate cancer, ≤T2a, prostate-specific antigen (PSA) <15 ng/mL, PSA density ≤0.2 ng/mL/cc, any International Society of Urological Pathology (ISUP) grade 1 are eligible. Men with ISUP grade 2 in <30% of cores on systematic biopsy and <10 mm cancer in one core on systematic or targeted biopsy are also eligible. Men diagnosed on systematic biopsy should have an MRI and targeted biopsies against Prostate Imaging and Reporting Data System V.2 3–5 lesions before inclusion. Identical follow-up in the two study arms: biannual PSA testing, yearly clinical examination and MRI every second year. In the experimental arm, standardised triggers based on MRI and PSA density elicit repeated biopsies. MRI and histopathological progression trigger radical treatment. Primary outcome measure is progression-free survival. Secondary outcome measures are cumulative incidence of metastatic disease, treatments with curative intent, pT3-4 at radical prostatectomy, switch to watchful waiting, prostate cancer mortality and quality of life. Inclusion started in October 2016 and in October 2018; 275 patients have been enrolled. Ethics and dissemination: Ethical approval was obtained in each participating country. Results for the primary and secondary outcome measures will be submitted for publication in peer-reviewed journals. Trial registration number: NCT02914873 .